2023
DOI: 10.5897/ajar2023.16311
|View full text |Cite
|
Sign up to set email alerts
|

On-farm participatory evaluation and selection of crop varieties at climate changes in Southern Niger

Alio Moussa Abdourazak,
Traore Bouba,
Sani Boubacar Gaoh Bassirou
et al.

Abstract: Participatory varietal selection (PVS) is one of the most rapid and cost-effective ways for breeders, farmers, and agronomists to identify high-yielding and well adapted varieties to current climate threats and to obtain feedback from the potential end users in the early phases of the breeding cycle (s). On the other hand, a participatory evaluation of improved and local varieties of pearl millet, sorghum, cowpea, and groundnut was conducted in Southern Niger during the growing seasons of 2020 and 2021. The fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…As observed in Table 2 , most farmers selected grain yield (83.33%), but was preferred by slightly more women (87%) than men (79%). Similar studies have consistently found preference for high grain yield among cowpea farmers (e.g., Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ). These studies ( Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ), however, assumed preference for traits among producers and end-users to be gender-blind, therefore did not consider trait preferences for both men and women.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As observed in Table 2 , most farmers selected grain yield (83.33%), but was preferred by slightly more women (87%) than men (79%). Similar studies have consistently found preference for high grain yield among cowpea farmers (e.g., Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ). These studies ( Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ), however, assumed preference for traits among producers and end-users to be gender-blind, therefore did not consider trait preferences for both men and women.…”
Section: Discussionsupporting
confidence: 61%
“…Similar studies have consistently found preference for high grain yield among cowpea farmers (e.g., Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ). These studies ( Rabé et al, 2022 ; Karikari et al, 2023 ; Moussa et al, 2023 ), however, assumed preference for traits among producers and end-users to be gender-blind, therefore did not consider trait preferences for both men and women. From the study, the finding that more women preferred pods that grow above the canopy for the reason that such cowpea are easier to harvest confirms ( Ridgeway, 2009 ; Sylla et al, 2023 ) that gender relations fit into social structures that define agricultural tasks.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation